Marriage and family relics of the past or promise of the future? - Augustin, George 1955- (Paulist Press, 2015)
"With the topics of marriage and family at the center of ecclesial attention, this new volume examines these issues in light of the ongoing discussions begun by Pope Francis with the Year of Faith celebration of family life and continuing through the Extraordinary General Assemblies of the Synod of Bishops. The result is an examination of the problems of marriage and family in the contemporary world, an examination which offers a better and more profound understanding of church doctrine."--Back cover